Leadership Styles and Generational Differences in Manufacturing and Service Organizations - Molek Nadia; Markič Mirko; Janežič Dušan; Lužar Magda; Brcar Franc (Organizacija, 2023)
The purpose of this study was to examine generational differences and leadership style preferences in service and manufacturing organizations in south-eastern (SE) Slovenia. The focus was on preferred leadership approaches and generational differences.